Trophic ecology shapes spatial ecology of two sympatric predators, the great hammerhead shark (Sphyrna mokarran) and bull shark (Carcharhinus leucas) - Lubitz, Nicolas; Abrantes, Kátya; Crook, Kevin; Currey-Randall, Leanne M.; Chin, Andrew; Sheaves, Marcus; Fitzpatrick, Richard; Barbosa Martins, Ana; Bierwagen, Stacy; Miller, Ingo B.; Barnett, Adam (Frontiers in Marine Science, 2023)
Information on how the trophic ecology of predators shapes their movement patterns and space-use is fundamental to understanding ecological processes across organisational levels. Despite this, studies combining spatial and trophic ecology to determine how prey preference and/or resource availability shape space use are lacking in marine predators as these can occur at low density and are often difficult to track over extended periods. Furthermore, many exhibit behavioural variability within species and among closely related, sympatric species adding further complexity. We applied a context-focused, multi-method approach to the understudied great hammerhead shark (Sphyrna mokarran) to test if movement and home ranges relate to prey preference and availability. Movement data from satellite and acoustic telemetry in Queensland, Australia, were combined with stable-isotope analysis, drone surveys, and videos of hunting behaviour. Limited dispersal, and small home ranges in S. mokarran were linked to trophic specialisation on stingray prey. Drone surveys and videos showed predation events on stingrays and demonstrated high, year-round availability of this prey in shallow, inshore habitats, which may allow the majority of S. mokarran to remain resident. This affinity for inshore habitats suggests that critical life-history requirements are performed over local or regional scales, although some larger movements were evident. These results were interpreted in comparison to the well-studied bull shark (Carcharhinus leucas), which showed reliance on pelagic food webs. Carcharhinus leucas had high individual variability in movement, with both large-scale migrations and residency. This could indicate that only some individuals are locally sustained on dynamic, pelagic food webs, while others undergo large-scale excursions over distant habitats. The specialised foraging of S. mokarran indicates they play an apex predator role in shallow, inshore habitats, potentially shaping space-use, and foraging behaviour of batoids. As inshore habitats are disproportionately affected by anthropogenic stressors, S. mokarran’s trophic specialisation and limited demographic connectivity may make the species particularly vulnerable to anthropogenic threats.